Komunikasi sebagai Dasar Optimalisasi Kinerja Karyawan - Aprih Santoso; Nirsetyo Wahdi (JUDICIOUS, 2022)
The study's objective was to investigate how communication affects telemarketing staff members at the Bank Sinar Mas Semarang Branch's performance, with work motivation serving as the mediating variable. The research population included all telemarketing employees of Bank SinarMas Semarang Branch, totaling 66 employees. The number of samples is 66 people. The sample selection method is census. The collected data were analyzed using AMOS-25. The study's findings utilizing the AMOS-25 method demonstrate that communication at Bank Sinar Mas Telemarketing Employees, Semarang Branch, has a favorable and significant impact on employee performance. Work motivation can be a mediating variable for communication's impact on Semarang Branch of Bank Sinar Mas Telemarketing Employees' performance.